Estudio comparativo de control PID y control Fuzzy en un proceso de flujo. - Ángel Steven, Real Garcés (2021)
In the following technological proposal, a resource is proposed which will make a comparison between a Classic Control such as the PID and a Modern Control such as the Fuzzy. Where through the respective implementation in the flow process, which will allow it to be controlled with large work margins since it is possible to exercise control in a non-linear range, which is not possible with a PID controller, through the use of a data acquisition card. FPGA data, as well as using OPC communication to transfer the data obtained from a PLC to Simulink, the technical responses obtained from the controlled variable will be verified, where the values obtained from both controllers can be observed, which will later be compared with each other, thus obtaining similarities and differences between each one of them without discrediting any of them in their functioning.